Egyptian Feminist Critiques of Neoliberalism - Elmalky, Asmaa (AUC Knowledge Fountain, 2026)
This research examines Egyptian feminist critiques of neoliberal economic policies through a Third World feminist and feminist political economy framework. It argues that neoliberalism in Egypt has produced controlling power dynamics through restructuring labor markets, social reproduction, and legal systems in ways that disproportionately impoverish women, particularly working-class women. The research maps diverse feminist engagements with neoliberal reforms, including structural adjustment programs, privatization, labor reduction, and legal liberalization. These critiques were influenced by the debates between Third World and transnational feminism, the thesis emphasizes the importance of national specific analysis in understanding how global neoliberal policies are mediated through national institutions, state power, and patriarchal social relations. Using Silvia Federici’s conceptualization of neoliberalism as a continuous process of primitive accumulation, the research highlights women’s unpaid reproductive labor and precarious waged work as central sites of capitalist accumulation. Through an analysis of labor law, personal status law, and international legal frameworks, the thesis demonstrates that law operates as a key mechanism in consolidating neoliberal and patriarchal power rather than protecting women. Most importantly, the paper explores Egyptian feminist scholarship as a critical intervention that exposes the structural roots of women’s impoverishment and challenges dominant narratives of neoliberal “empowerment.”